Effects of recyclable ceramsite as the porous bulking agent during the continuous thermophilic composting of dairy manure. (20th April 2019) - Li, Xu; Shi, Xiao-Shuang; Yang, Zhi-Man; Xu, Xiao-Hui; Guo, Rong-Bo
Abstract: Porous materials have been widely used as the bulking agent during the composting of organic waste. In this study, ceramsite, a cheap and recyclable material with good porosity, was firstly utilized during continuous thermophilic composting (CTC) of dairy manure. Five treatments were designed using the same mixture of dairy manure and corn straw with different dosage of ceramsite blending (0%, 5%, 10%, 15% and 20% on wet basis). 15% ceramsite containing group has exhibited the fastest waste decomposition. Whereas the group containing 20% ceramsite performed best in reduction of NH3 emission, but had the least organic matter loss. In addition, comparative studies within the groups supplemented with first, second and third used ceramsite were conducted. Compared with the first used ceramsite, the organic matter loss increased from 37.8% to 41.0%, the amount of cumulative CO2 increased from 113.62 to 124.01 mg·g −1 -TS, the reduction of cumulative NH3 increased from 8% to 21% and the germination index increased from 102.6% to 128.9% in group added with the third used ceramsite. Chloroform-fumigation extraction results revealed that the addition of recycled ceramsite led to a much higher microbial biomass carbon during the composting process. Also FTIR spectra of ceramsite exhibited the total acid functional groups increased on the second and third used ceramsite, implying stronger adsorption to NH4 + and NH3 . The better results were observed with the increasing of ceramsite recycled times in accelerating the biodegradation of the organic waste, reducing NH3 emission and increasing the compost maturity. Graphical abstract: Image 10162046 Highlights: Ceramsite was firstly used as the bulking agent during composting. The addition of ceramsite could accelerate the composting process and reduce NH3 emission. The recycled ceramsite exhibited better effects than the first used ceramsite. Addition of the recycled ceramsite was beneficial for the growing of microbes. The total amount of acid groups on the ceramsite increased with the recycling of ceramsite.